Effects Of Using Expressive Arts Therapy In Group Counseling On Managing Delinquent Adolescents' Anger - Nor Hamizah Ab Razak; Sabihah Johan; Ku Suhaila Ku Johari; Sh Marzety Adibah Al Sayed Mohamad; Nadziroh Md Zubir (Human Resource Management Academic Research Society, 2024)
Expressive arts theraphy is a multimodal therapy of art that is practiced as an individual psychological recovery process. The purpose of this study was to identify the effects of expressive art therapy in group counseling on delinquent adolescents’ anger. Quasi-experimental designed with pre and post test methods are used in this study. A total of 84 delinquent adolescents living in moral rehabilitation institutions, aged 14 to 21 years old were selected using purposeful sampling. Clinical Anger Scale (CAS) is used to measure the dependent variable and supported by the analysis of documents. The results showed that there was a significant reduction in adolescents’ anger. Research implications are discussed from theoretical aspects, counselling professionals, other researchers and Social Welfare Department. In short, Expressive Arts Therapy has been an alternative to expressing latent feelings and an effective communication medium.